1993
DOI: 10.1258/002367793780745381
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oestrus in cats by photoperiodic manipulations and social stimuli

Abstract: SummaryThe development of the nervous system can be studied only if the age of the embryo is exactly known. Since it is difficult to control reproduction in female cats, we tried to time fertilization very precisely to within one hour by using either artificial insemination, or by mating females in oestrus induced by light programming.In one trial, this programming was associated with male or female stimuli according to the work of McClintock (1971McClintock ( , 1978McClintock ( , 1984 and Preti et al. (1986).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
6

Year Published

2003
2003
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 8 publications
0
29
0
6
Order By: Relevance
“…In this study, the duration (days) of estrus was not investigated, but considering that the mean duration is 7 days [6,11,12,14,16], the interestrus interval is 24 days (31 days-7 days). The interval is different from values reported by Michel [10], Shille et al [14], and Wildt et al [16]. There was no relationship between the number of estrous cycles and the duration of the breeding season, suggesting that the interestrus interval differs noticeably among individual animals, but Lawler et al [7] found that individual acclimation led to spontaneous ovulation in a high proportion of cats.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, the duration (days) of estrus was not investigated, but considering that the mean duration is 7 days [6,11,12,14,16], the interestrus interval is 24 days (31 days-7 days). The interval is different from values reported by Michel [10], Shille et al [14], and Wildt et al [16]. There was no relationship between the number of estrous cycles and the duration of the breeding season, suggesting that the interestrus interval differs noticeably among individual animals, but Lawler et al [7] found that individual acclimation led to spontaneous ovulation in a high proportion of cats.…”
mentioning
confidence: 72%
“…Leyva et al [9] reported that no recurrent estrus occurred after melatonin was administered to cats under 24-hr lighting. No recurrent estrus occurs under 8-hr lighting in the cat room, whereas estrus recurs under 12-hr lighting [4,8,10,13,14]. Therefore, it is recommended that the lighting cycle should be 14 hr or more for cat breeding [10,12,14].…”
mentioning
confidence: 99%
“…Group housing, especially the introduction of a tomcat or estral queen, provides social stimuli that hasten the onset of estrus (Michel, 1993). In addition to age, factors that affect the onset of puberty include breed, time of year or photoperiod, social environment, health, physical condition, and nutritional status.…”
Section: A Reproductive Biologymentioning
confidence: 99%
“…For example, Siberian hamsters and meadow voles lose fat mass and total body weight (BW) with shortened days [3,4], while Syrian hamsters, collared lemmings, prairie voles and raccoon dogs gain fat mass and total BW with SD [5-8]. Cats are sensitive to photoperiod as it relates to circulating melatonin concentrations and estrous cycling [9-11] and seasonal differences in activity levels are known to exist in feral cat populations, with increased activity during the spring/summer period [12]. Seasonal and photoperiod changes on energy intake, energy expenditure, and voluntary physical activity levels have also been recently reported in domestic cats [13,14].…”
Section: Introductionmentioning
confidence: 99%